Service and manufacturing knowledge in product-service systems: a case study - Doultsinou, Athanasia; Baxter, David; Roy, Rajkumar; Gao, James X.; Mann, A. (Cranfield University Press, 2009)
In the developing Product-Service Systems (PSS) field, an emerging research challenge is supporting the PSS design activity. This paper presents a case study in which manufacturing and service knowledge is captured and classified in order to support the design activity. A knowledge capture exercise took place to identify manufacturing and service knowledge applied in the design process. A design knowledge capture exercise led to the creation of a design process model. The case study reports on the proposed structure for the application of manufacturing and service knowledge to a conceptual and a detailed design task. The knowledge framework is implemented using the Protégé knowledge base editor. PSS design requires an integrated system level approach to design, and therefore a system level knowledge structure is required. The detailed case study indicates where manufacturing and service knowledge is applied in the design activity, which is divided into ‘conceptual’ and ‘detailed’ stages.
Organised by: Cranfield University
Keywords: Product-service systems; service knowledge; manufacturing knowledge; design